The Effects of Newcastle Disease Virus (NDV) On Breast Cancer Cell Lines - Mohamad Wali, Haryati Shila (2003)
Three Newcastle disease virus (NDV) isolates namely; F, Ijuk and 0l/C were tested for their anticancer properties against two breast cancer cell lines, MCF-7 and MDA-MB-231. Each virus strain was propagated in 10-day old embryonated eggs. Purification was carried out by density gradient centrifugation using sucrose. The titer of each virus strain was determined by hemagglutination (HA) test. Screening of NDV strains for anticancer properties on breast cancer cells was performed by a colorimetric cytotoxic assay using tetrazolium salt (MTT). F strain displayed cytotoxic activity on both breast cancer cells with an IC50 value of 8 HAU for MDA-MB-231 cells and 2048 HAU for MCF-7 cells. Meanwhile Ijuk showed cytotoxic activity against MDA-MB-231 cells only with an IC50 value of 8.6 HAD. Strain 01/C did not exhibit any cytotoxic activity towards both breast cancer cells. Inactivation of the virus at 100°C for 30 minutes destroyed its ability to kill the breast cancer cells. Positive control experiment involved treatment of the cells with tamoxifen, an estrogenic antagonist agent. Negative control experiment was carried out by infecting the virus onto normal mouse fibroblasts (3T3 cell). No cytotoxic activity was observed on 3T3 cells following infection at low virus titer. However, infection at higher virus titer resulted in 50% inhibition of cell growth. Infection of the virus displayed clear evidence of apoptosis which was detected as a ladder-like pattern on agarose gel electrophoresis. This was further confirmed by TEM which provided ultrastructural changes of the infected cells. The role of sialic acid receptor was also studied based on neuraminidase (NA) and sialyllactose (SLL) treatment. Treatment of the cells with NA did not destroy the ability of the virus to cause apoptosis. Meanwhile a reduction in the ability of the virus to cause apoptosis was observed in the treatment of SLL. However there was no significant difference between the SLL-treated virus (27.05%) and untreated virus (30.87%). Based on the results obtained, this study showed that NDV strains, F and ljuk have the potential to be developed as an anticancer agent. Mechanisms by which the virus infects and kills the cells need further studies. The role of sialic acid receptors in NDV-induced oncolytic effects requires further studies.